Patterns of sperm storage in twice-mated Queensland fruit flies. (August 2021) - Shadmany, Jason; Lee, Siu F.; Taylor, Phillip W.
Graphical abstract: Highlights: Sperm storage by twice-mated female Queensland fruit fly was assessed. Lines fixed for 3 SSR alleles were developed for sperm counting and genotyping. Females stored fewer sperm from their second mate than from their first mate. Number and asymmetry of sperm from first mates constrained storage of second mates. Limits of spermathecal capacity affect sperm storage patterns. Abstract: Polyandry, whereby females mate with more than one male in a reproductive cycle, can result in sperm competition or cryptic female choice, and have fitness implications for both sexes. Understanding patterns of sperm storage in twice-mated females can provide valuable insights to mechanisms that mediate sperm use and paternity. In the Queensland fruit fly, Bactrocera tryoni (Qfly), and other insects that are managed by the Sterile Insect Technique (SIT), polyandry can reduce the efficacy of this pest control method. Patterns of sperm storage in twice-mated Qflies were studied by developing three fly lines that are homozygous for different alleles of a microsatellite marker ( Bt32 ) and using a combination of quantitative real time polymerase chain reaction (qPCR) and capillary electrophoresis-based techniques to quantify and genotype sperm in each spermatheca. Female Qflies consistently stored fewer sperm from their second mate than from their first mate. Further, asymmetry between the spermathecae in the distribution of sperm stored from the first mate appears to in part determine the distribution of sperm stored from the second mate, likely because of constraints in storage capacity in the two spermathecae. Implications of these findings for elucidating pattern of sperm competition in this species, and for SIT, are discussed.